2020
DOI: 10.4236/ojapps.2020.1011053
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Scar Acceleration Method - Mac<sup>®</sup> in the Treatment of Vulvovaginal Candidiasis: A Proposal for Treatment in Public Health in Sus, Brazil

Abstract: Vulvovaginal candidiasis is an infection of the genital mucosa, which involves the vulva and vagina caused by yeast. It is considered a recurrent pathology and a public health problem that causes discomfort by the triggers and that, when left untreated, can lead to health problems. The present study is a report of two cases treated with the MAC ®-Scar Acceleration Method-(MAC ®) methodology at the Physiotherapy School Clinic of Teaching Center of Campos Gerais (CESCAGE) as a pilot for the proposal to implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In addition, one case report has shown that treatment with methylene blue (660 nm red laser) for PDT of vulvovaginal candidiasis significantly decreased fungal infection in the vaginal canal. This report claimed that this therapy improved the quality of life of patients who reported a reduction in symptoms [98]. Moreover, antifungal blue light therapy (400-470 nm) has been reported to be effective in decreasing vaginal candidiasis.…”
Section: Pdt For Fungal Stismentioning
confidence: 95%
“…In addition, one case report has shown that treatment with methylene blue (660 nm red laser) for PDT of vulvovaginal candidiasis significantly decreased fungal infection in the vaginal canal. This report claimed that this therapy improved the quality of life of patients who reported a reduction in symptoms [98]. Moreover, antifungal blue light therapy (400-470 nm) has been reported to be effective in decreasing vaginal candidiasis.…”
Section: Pdt For Fungal Stismentioning
confidence: 95%
“…The MAC ® method uses photodynamic therapy with the use of photopharmaceuticals, cellular markers and the use of correct parameters for each case inducing the acceleration of tissue repair. Photodynamic therapy (PDT) is a photochemical that uses light to activate specific chemicals that, in the activated state, confer cytotoxicity (Pinto, et al, 2020) [5].…”
Section: Introductionmentioning
confidence: 99%